Health workforce demography: a framework to improve understanding of the health workforce and support achievement of the Sustainable Development Goals - Szabo, Sylvia (Hum Resour Health, 2020)
The ambition of universal health coverage entails estimation of the number, type and distribution of health workers required to meet the population need for health services. The demography of the population, including anticipated or estimated changes, is a factor in determining the ‘universal’ needs for health and well-being. Demography is concerned with the size, breakdown, age and gender structure and dynamics of a population. The same science, and its robust methodologies, is equally applicable to the demography of the health workforce itself. For example, a large percentage of the workforce close to retirement will impact availability, a geographically mobile workforce has implications for health coverage, and gender distribution in occupations may have implications for workforce acceptability and equity of opportunity. In a world with an overall shortage of health workers, and the expectation of increasing need as a result of both population growth in the global south and population ageing in the global north, studying and understanding demographic characteristics of the workforce can help with future planning. This paper discusses the dimensions of health worker demography and considers how demographic tools and techniques can be applied to the analysis of the health labour market. A conceptual framework is introduced as a step towards the application of demographic principles and techniques to health workforce analysis and planning exercises as countries work towards universal health coverage, the reduction of inequities and national development targets. Some illustrative data from Nepal and Finland are shown to illustrate the potential of this framework as a simple and effective contribution to health workforce planning.